PENDEKATAN SAINTIFIK DENGAN METODE ROLE PLAYING MEMPERMUDAH PENILAIAN INDIVIDU PESERTA DIDIK - Budi Sasomo (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2015)
The reseach was aimed to find the teacher’s solution in assessing the students individually and authentically. The research used the method from literature review to get the problems of statement, the data collection, explanation, and creating conclusion and suggestion. The result of literature review was the steps of learning, those are: 1) Pre – learning activity which has observation, problems statement, problem reasoning and solution creating 2) Learning activity covered demonstrating the role (communicate) which was prepared, observating and evaluating each performance. Therefore, learning using combination between scientific approach and role playing method will ease the teacher in assessing the students in three aspects of learning assessment based on curriculum 2013.